Lesson learned from the COVID-19 pandemic: toddlers learn earlier to read emotions with face masks - Gori, Monica; Schiatti, Lucia; Faggioni, Monica; Amadeo, Maria Bianca (Frontiers in Psychology, 2024)
In a prior study we demonstrated that the presence of face masks impairs the human capability of accurately inferring emotions conveyed through facial expressions, at all ages. The degree of impairment posed by face covering was notably more pronounced in children aged between three and five years old. In the current study, we conducted the same test as a follow-up after one year from the onset of the COVID-19 pandemic, when the requirement of wearing face masks was holding in almost all circumstances of everyday life when social interactions occur. The results indicate a noteworthy improvement in recognizing facial expressions with face masks among children aged three to five, compared to the pre-pandemic settings. These findings hold a significant importance, suggesting that toddlers effectively mitigated the social challenges associated with masks use: they overcame initial environmental limitations, improving their capability to interpret facial expressions even in the absence of visual cues from the lower part of the face.